Investigating the Impact of Digital Learning on Academic Achievements of Young Learners in Voinjama City - Forkpah, Eric; Barazon, Leviticus (JOSEE : Jurnal Intelektual Mahasiswa, 2023)
The purpose of this study is to look at the impact of digital learning on preschool academic achievement in Voinjama City, Lofa County, Liberia. The study, which included 20 participants, found that financial constraints as well as educational problems. A significant 40% of respondents, however, indicated a positive impact on academic attainment. The findings shed light on the complicated dynamics of digital learning in the context of early childhood education in Liberia. Despite economic limits and pedagogical challenges, the observed gain in academic performance demonstrates that digital learning interventions may be effective. These findings are critical for improving and optimizing digital learning practices in preschool education, as well as alerting educators, policymakers, and stakeholders in Voinjama City about the obstacles and opportunities associated with incorporating technology into the early childhood learning environment. Liberia continues to navigate advancements in education, understanding the impact of digital learning on preschoolers' academic achievement becomes imperative for fostering a more effective and inclusive early education system.